2018
DOI: 10.1016/j.tmrv.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Tanzania's National Met and Unmet Blood Demand From a Survey of a Representative Sample of Hospitals

Abstract: Estimating blood demand to determine collection goals challenges many low-income countries. We sampled Tanzanian hospitals to estimate national blood demand. A representative sample based on probability proportional to size sampling of 42 of 273 (15%) Tanzanian transfusing hospitals was selected. Blood bank registers, patient medical records, and blood component disposition records were reviewed prospectively from June to September 2013 to determine the number of components requested and the number and proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…Data from 10 studies that reported on general patient populations were considered for analysis of the primary outcome, but only six studies could be used for this analysis because two did not report specific diagnostic categories and the other two did so using International Classification of Diseases, 10th Revision (ICD‐10) disease categories (Appendix S3.2). We found that among the general patient population, the majority of blood products were used for the following diagnostic categories: pediatric malaria (20%), sickle cell anemia (18%), obstetric hemorrhage (16%), and other causes of bleeding (16%), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 10 studies that reported on general patient populations were considered for analysis of the primary outcome, but only six studies could be used for this analysis because two did not report specific diagnostic categories and the other two did so using International Classification of Diseases, 10th Revision (ICD‐10) disease categories (Appendix S3.2). We found that among the general patient population, the majority of blood products were used for the following diagnostic categories: pediatric malaria (20%), sickle cell anemia (18%), obstetric hemorrhage (16%), and other causes of bleeding (16%), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Main considerations for sample size included available resources, logistics, and statistical precision of the estimates. 31 Statistical analyses were conducted with computer software (SAS, Version 9.3, SAS Institute) accounting for the design features and weights for the survey. This included specification of strata, clusters, survey weights, and strata totals for finite population consideration.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation procedure takes this into account in terms of sampling weights to calculate the national estimate with statistically correct standard error (SE) estimates to reflect the variation due to sampling. Drammeh and colleagues provide details of the estimation procedure. The sample was selected using rigorous and well‐established sampling methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of Tanzanian transfusion services, 37.5% of blood components were issued by blood banks outside of the NBTS. 104…”
Section: External Funding For Transfusion Safetymentioning
confidence: 99%